Beyond DNA: An Integrated and Functional Approach for Classifying Germline Variants in Breast Cancer Genes. (16th October 2016) - Pesaran, T.; Karam, R.; Huether, R.; Li, S.; Farber-Katz, S.; Chamberlin, A.; Chong, H.; LaDuca, H.; Elliott, A.
Abstract : Genetic testing for hereditary breast cancer is an integral part of individualized care in the new era of precision medicine. The accuracy of an assay is reliant on not only the technology and bioinformatics analysis utilized but also the experience and infrastructure required to correctly classify genetic variants as disease-causing. Interpreting the clinical significance of germline variants identified by hereditary cancer testing is complex and has a significant impact on the management of patients who are at increased cancer risk. In this review we give an overview of our clinical laboratory's integrated approach to variant assessment. We discuss some of the nuances that should be considered in the assessment of genomic variants. In addition, we highlight lines of evidence such as functional assays and structural analysis that can be useful in the assessment of rare and complex variants.